THE INFLUENCE OF SHOPPING LIFESTYLE, BRAND AMBASSADOR, AND E-PROMOTION ON CONSUMER PURCHASE DECISIONS FOR ARINNA PREMIUM HIJAB PRODUCTS WITH CONSUMER RELIGIOSITY AS A MODERATING VARIABLE - Faridhatul Jannah; Ubaidullah Muayyad (STAI Nusantara Kota Banda Aceh, 2026)
This research is conducted to examine the effects of Shopping Lifestyle, Brand Ambassador, and E-Promotion on Purchasing Decisions, with Consumer Religiosity functioning as a moderating variable. A quantitative research design was applied using a survey method, involving the distribution of questionnaires to 150 respondents. The data were analyzed using the SEM-PLS technique. The findings indicate that Shopping Lifestyle exerts a positive and statistically significant influence on Purchasing Decisions (coefficient = 0.244; T-statistic = 1.94; P-value = 0.026 < 0.05). In contrast, Brand Ambassador (coefficient = 0.008; T-statistic = 0.08; P-value = 0.468) and E-Promotion (coefficient = 0.140; T-statistic = 1.64; P-value = 0.051) do not demonstrate significant effects. Furthermore, moderation analysis reveals that Consumer Religiosity weakens the relationship between Shopping Lifestyle and Purchasing Decisions (coefficient = -0.245; T-statistic = 2.245; P-value = 0.012), while it does not significantly moderate the effects of Brand Ambassador or E-Promotion. Overall, the study concludes that internal consumer characteristics play a more dominant role than external influences in shaping purchasing decisions.